2018
DOI: 10.1016/j.jaci.2017.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Mannose receptor modulates macrophage polarization and allergic inflammation through miR-511-3p

Abstract: Background Mannose receptor (MRC1/CD206) has been suggested to mediate allergic sensitization and asthma to multiple glycoallergens, including cockroach allergens. Objective We sought to determine the existence of a protective mechanism through which MRC1 limits allergic inflammation through its intronic miR-511-3p. Methods We examined MRC1-mediated cockroach allergen uptake by lung macrophages and lung inflammation using C57BL/6 wild-type (WT) and Mrc1−/− mice. The role of miR-511-3p in macrophage polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
92
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 53 publications
5
92
0
Order By: Relevance
“…In particular, Mrc1-deficient mice showed significant reduction in CRE uptake, but unexpectedly, these mice have an exacerbation of CRE-induced airway inflammation. Although the underlying mechanisms remain uncertain, our studies suggest that Mrc1 deficiency in macrophages may lead to the alterations in allergen uptake and balance between classically activated (or M1) and alternatively activated (or M2) macrophage phenotypes (10) that may contribute to the exacerbation of airway inflammation.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…In particular, Mrc1-deficient mice showed significant reduction in CRE uptake, but unexpectedly, these mice have an exacerbation of CRE-induced airway inflammation. Although the underlying mechanisms remain uncertain, our studies suggest that Mrc1 deficiency in macrophages may lead to the alterations in allergen uptake and balance between classically activated (or M1) and alternatively activated (or M2) macrophage phenotypes (10) that may contribute to the exacerbation of airway inflammation.…”
Section: Introductionmentioning
confidence: 85%
“…C-type lectin receptors (CLRs) are pattern-recognition receptors that recognize allergenic glycans present on allergens, facilitating the endocytosis and presentation of pathogens that are critical in shaping the development of allergic asthma (1)(2)(3)(4)(5)(6)(7)(8). Most importantly, macrophage mannose receptor (MRC1/CD206), one of the major CLRs, has been shown to play an important role in mediating allergic sensitization (9,10), lung inflammation (10), and activation of innate immune cells (4,11). Our previous studies identified a critical role of MRC1 in allergen clearance as a natural defense mechanism and in limiting the progression and severity of allergic inflammation induced by cockroach allergen (cockroach extract, CRE) in a mouse model of asthma (10).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations